CHEMICAL AND ORGANOLEPTIC PROPERTIES CHARACTERIZATION OF RICE ANALOG MADE FROM MOCAF, BANANA OR CORN WITH ADDITION OF MUNG BEAN FLOUR - Taufik Hidayat; Wilda Mikasari; Shannora Yuliasari; Lina Ivanti; Taupik Rahman (Jurnal Agroindustri, 2020)
Rice analog made from locally available flour is one of food diversification to reduce rice consumption. Locally available flour that could be used to make rice analog is mocaf, kepok banana and corn. This study aims to formulate and analyses characteristic of rice analog made from mocaf, kepok banana and corn with addition of mung bean flour. This study using laboratory analysis and consumer preference test. This study divided into three stages; 1. Formulation of rice analog; 2. analysis of chemical characteristic of rice analog; 3. consumer preference test to the rice analog. Observed parameter are chemical characteristic consist of water content, protein, carbohydrate, fat and fiber while the organoleptic characteristic is color, aroma, texture and flavor. Observed data were statistically tested using analysis of variance. The study showed that utilization of mocaf, kapok, banana and corn to make rice analog produce rice analog with different color and texture. The best formula to produce rice analog based on organoleptic test is formula using mocaf flour 80% with mung bean flour 20%. Chemical analysis of rice analog using mocaf flour were protein content 8.24%; fat 0.73%; carbohydrate 77.97%; fiber 1.87%, water 9.72% and ash 1.47%. Organoleptic test showed that consumer preference towards rice analog made from modified cassava flour (mocaf) higher than other rice analog.